Dynamic stroma reorganization drives blood vessel dysmorphia during glioma growth. Issue 12 (16th October 2017) - Mathivet, Thomas; Bouleti, Claire; Van Woensel, Matthias; Stanchi, Fabio; Verschuere, Tina; Phng, Li‐Kun; Dejaegher, Joost; Balcer, Marly; Matsumoto, Ken; Georgieva, Petya B; Belmans, Jochen; Sciot, Raf; et al.
Abstract: Glioma growth and progression are characterized by abundant development of blood vessels that are highly aberrant and poorly functional, with detrimental consequences for drug delivery efficacy. The mechanisms driving this vessel dysmorphia during tumor progression are poorly understood. Using longitudinal intravital imaging in a mouse glioma model, we identify that dynamic sprouting and functional morphogenesis of a highly branched vessel network characterize the initial tumor growth, dramatically changing to vessel expansion, leakage, and loss of branching complexity in the later stages. This vascular phenotype transition was accompanied by recruitment of predominantly pro‐inflammatory M1‐like macrophages in the early stages, followed by in situ repolarization to M2‐like macrophages, which produced VEGF‐A and relocate to perivascular areas. A similar enrichment and perivascular accumulation of M2 versus M1 macrophages correlated with vessel dilation and malignancy in human glioma samples of different WHO malignancy grade. Targeting macrophages using anti‐CSF1 treatment restored normal blood vessel patterning and function. Combination treatment with chemotherapy showed survival benefit, suggesting that targeting macrophages as the key driver of blood vessel dysmorphia in glioma progression presents opportunities to improve efficacy of chemotherapeutic agents. We propose that vessel dysfunction is not simply a general feature of tumor vessel formation, but rather an emergent property resulting from a dynamic and functional reorganization of the tumor stroma and its angiogenic influences. Synopsis: Dynamic multi‐photon imaging and genetic labeling and targeting in an orthotopic tumor model reveals that progressive changes in stromal cells are the leading cause of vascular dysmorphia in glioma. Initial tumour growth is accompanied by functional vessel patterning. Progressive blood vessel dysmorphia coincides with bone‐marrow derived macrophage recruitment. M2‐polarized macrophages accumulate around tumour blood vessels in glioma progression in mouse and with increasing WHO grades in humans. Depleting macrophages or their VEGF production restore blood vessel caliber and function. Macrophages depletion enhances efficacy of chemotherapeutic agents. Abstract : Dynamic multi‐photon imaging and genetic labeling and targeting in an orthotopic tumor model reveals that progressive changes in stromal cells are the leading cause of vascular dysmorphia in glioma.